Drainage of middle lobe vein into anomalous right lower lobe vein: management during thoracoscopic lobectomy - Dario Amore; Alessandro Saglia; Dino Casazza; Tullio Valente; Pasquale Imitazione; Carlo Curcio (Respirology Case Reports, 2020)
Abstract Variations in pulmonary venous anatomy should not be underestimated by thoracic surgeons prior to or during major lung resections in order to avoid serious surgical complications. Here, we report a case of middle lobe vein draining into a right inferior lobar vein formed by two anomalous trunks lying on the superior surface of the common basal bronchus: in such instance, to avoid compromising the middle lobe vein drainage during a thoracoscopic right lower lobectomy, the two main tributaries of the lower lobe vein were individually identified and dissected peripherally from the anterior aspect after division of the major fissure. A careful hilar dissection and a precise surgical strategy can help surgeons perform correct procedures in presence of pulmonary vascular anomalies.